Extended convex hull-based distributed optimal energy flow of integrated electricity-gas systems. (1st April 2021) - Liu, Rong-Peng; Sun, Wei; Yin, Wenqian; Zhou, Dali; Hou, Yunhe
Highlights: A distributed optimization model for integrated electric-gas systems is established. The proposed model is convexified by the extended convex hull-based method. The convexified model is solved by a multi-block distributed algorithm. A solution feasibility check and recovery method is proposed. Abstract: Integrated electricity and gas systems are constructed to facilitate the gas-fired generation, and the distributed operation of these integrated systems have received much attention due to the increased emphasis on data security and privacy between different agencies. This paper proposes an extended convex hull based method to address optimal energy flow problems for the integrated electricity and gas systems in a distributed manner. First, a multi-block electricity-gas system model is constructed by dividing the whole system into N blocks considering both physical and regional differences. This multi-block model is then convexified by replacing the nonconvex gas transmission equation with the extended convex hull-based constraints. The Jacobi-Proximal alternating direction method of multipliers algorithm is adopted to solve the convexified model and minimize its operation cost. Finally, the feasibility of the optimal solution for the convexified model is checked, and a sufficient condition is developed. If the sufficient condition is satisfied, the optimal solution for the original nonconvex problem can be recovered from that for the convexified problem. Simulation results demonstrate that the proposed method is tractable and effective in obtaining feasible optimal solutions for multi-block optimal energy flow problems.